2015
DOI: 10.1016/j.foodchem.2015.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of processed meat products by peptidomic analysis using rapid ambient mass spectrometry

Abstract: . (2015) Authentication of processed meat products by peptidomic analysis using rapid ambient mass spectrometry. Food Chemistry, Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/48918/2/FoodChem_08-03-2015.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the University of Nottingham End User licence and may be reused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…According to Hofmann (9), meat proteins are not truly degraded during heating but they lose dye-binding basic groups, which means that the protein is still present in the gel, although its ability to be stained is reduced. However, in our previous studies we observed lower MASCOT scores and sequence coverages in processed meat than in raw meat (12,13). This indicates that meat proteins undergo irreversible degradation during thermal treatment and industrial processing, which may aff ect mass spectrometry--based studies.…”
Section: Aggregation Of Meat Proteinsmentioning
confidence: 75%
See 2 more Smart Citations
“…According to Hofmann (9), meat proteins are not truly degraded during heating but they lose dye-binding basic groups, which means that the protein is still present in the gel, although its ability to be stained is reduced. However, in our previous studies we observed lower MASCOT scores and sequence coverages in processed meat than in raw meat (12,13). This indicates that meat proteins undergo irreversible degradation during thermal treatment and industrial processing, which may aff ect mass spectrometry--based studies.…”
Section: Aggregation Of Meat Proteinsmentioning
confidence: 75%
“…Washing, digestion and mass spectrometry analysis were performed according to the procedure described previously (13). Thin sections of raw and cooked meat and meat products (slices of 0.5 g) were transferred to glass vials and washed to remove contaminants such as physiological salts, fat and other so luble low-molecular-mass compounds.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a study, ambient liquid extraction surface analysis mass (LESA-MS) was utilized to differentiate complex mixtures of processed proteins/peptides from bovine, porcine, horse, chicken and turkey meat (Montowska et al, 2015). It is mentioned that they have detected protein-specific heat stable peptide markers in processed food samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the year 2013, the horse meat scandal in Europe and rat meat scandal in China led to concerted efforts in the detection, differentiation and identification of meat species in meat and meat products (Mohamad, El-Sheikha, Mustafa, & Mokhtar, 2013). Recent studies have revealed 68% mislabeling in sausages, burger patties and meats collected from butcheries and retail outlets in South Africa, 33% seafood in USA, and 24.7% in luxury processed meat products in Poland (Montowska, Alexander, Tucker, & Barrett, 2015). Nevertheless, meat authentication is still a topic of debate and, therefore, honest and accurate labeling of food is an essential component of food safety.…”
Section: Introductionmentioning
confidence: 99%